2019
DOI: 10.1007/s00167-019-05474-7
|View full text |Cite
|
Sign up to set email alerts
|

Mid-flexion laxity in the asymptomatic native knee is predominantly present on the lateral side

Abstract: Purpose During total knee arthroplasty (TKA), an orthopaedic surgeon is focused on soft-tissue balance in extension (0°) and in lexion (90°). Patients with instability problems of the knee often report a feeling of instability during daily life activities, at around 30° knee lexion. There are no reference values available for knee laxity of healthy subjects in mid-lexion (30°) and lexion (90°) for comparison with the TKA population. Therefore, the aim was to quantify varus and valgus knee laxity in extension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…40 In both flexion and extension, medial (valgus) laxities are less than lateral (varus), with the medial side being more isometric and constrained. 40,41 The lateral (varus) laxities increase in higher degrees of knee flexion. 42 In the context of TKA, PCL resection produces a greater increase in the flexion gap relative to the extension gap, and also increases lateral laxities more than medial.…”
Section: Overviewmentioning
confidence: 99%
“…40 In both flexion and extension, medial (valgus) laxities are less than lateral (varus), with the medial side being more isometric and constrained. 40,41 The lateral (varus) laxities increase in higher degrees of knee flexion. 42 In the context of TKA, PCL resection produces a greater increase in the flexion gap relative to the extension gap, and also increases lateral laxities more than medial.…”
Section: Overviewmentioning
confidence: 99%
“…The result obtained in terms of HKAa showed higher repeatability for the measurements at the flexion angles typically taken as reference during the calibration (0° and 90°) [ 21 ], hence justifying this choice as they are able to provide reliable and robust info on which base the surgical cuts. Flexion angles like 30° and 60°, on the other hand, suffer the effects of the so called mid-flexion instability [ 21 ] and therefore are characterized by higher variability if compared to full-extension and 90° configurations, but it is noticeable that also in these sub-optimal cases the comparison did not return remarkable differences.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al reported that patient‐reported pain and instability were adversely affected by greater laxity [18], while Kamenaga et al found greater lateral laxity at extension significantly correlated with better patient satisfaction [37]. In healthy knees, it is generally recognized that the lateral knee shows greater laxity than the medial knee due to the medial‐pivot motion [38]. Our study revealed that the longer the LCL length and the higher the elongation rate during mid flexion, the better the Knee Score of the MP patients.…”
Section: Discussionmentioning
confidence: 99%